Exploring subspace-constrained approaches to low-rank fMRI acceleration - Mason, HT (2020)
Functional magnetic resonance imaging (fMRI) is a medical imaging technique that measures brain activity non-invasively. One of the fundamental quandaries in fMRI is the balance that must be struck between spatial fidelity and temporal resolution. An increase in sampling efficiency could improve either or both of these metrics, allowing images to be created from fewer data points than would otherwise be required. This process is referred to as acceleration.